PERAN TABLET CURCUMA DALAM MENURUNKAN RISIKO HEPATOTOKSISITAS PADA PASIEN TB PARU YANG MENJALANI TERAPI OAT DI RS PASAR REBO KOTA JAKARTA TIMUR - Dini Permata Sari; Nhila Putri Evani; Rangki Astiani (Journal Pharma Saintika, 2025)
Abstract: Curcuma is known to play a role in preventing the side effects of anti-tuberculosis drugs (OAT), including hepatotoxicity, by protecting liver cells from oxidative stress and inflammation induced by drugs. The objective of this study was to determine the relationship between Curcuma tablet supplementation and the level of liver damage (hepatotoxicity), as measured by AST, ALT, and total bilirubin levels in pulmonary tuberculosis patients at Pasar Rebo Hospital. This study was non-experimental and classified as an analytical study with a cross-sectional approach. Data collection was conducted retrospectively, by reviewing past medical data and events. The sample in this study consisted of a portion of pulmonary tuberculosis patients undergoing OAT therapy at Pasar Rebo Hospital, East Jakarta, during the period of January–December 2024. The results showed that Curcuma tablet supplementation provided significant benefits to the liver health of pulmonary TB patients, as indicated by a statistically significant decrease in AST, ALT, and total bilirubin levels (p < 0.05) after treatment. This decrease in liver enzyme and bilirubin levels reflects improved hepatic function and reduced hepatotoxicity. Thus, Curcuma tablets have been proven effective as a hepatoprotective agent in the context of OAT therapy..